Optimisation of copper ion removal using immobilised red seaweed of Euchema Cottonii Sp. in a packed-bed filter via Response Surface Methodology (RSM) - Nadiah, Mokhtar; Nur Afrina Damia, Mohd Noor Afizi; S., Mohd Zaki; H, Shukor; A., Aris (IOP Publishing Ltd., 2025)
Heavy metal contamination is emerging as a critical environmental concern, particularly in lower to middle-income countries where rapid industrialization, inadequate waste management, and limited regulatory oversight exacerbate the problem. For this reason, the treatment of heavy metal removal by biosorption was studied using a biosorbent derived from the Malaysia local red seaweed of Eucheuma Cottonii sp. The primary objective of this study was to optimise the performance of E.Cottonii sp. for copper removal via Response Surface Methodology-Central Composite Design (RSM-CCD). The seaweed immobilisation was prepared using 3% (w/v) of sodium alginate. Additionally, the raw and immobilised E.Cottonii sp. before and after biosorption were characterised by Scanning Electron Microscopy with Energy Dispersive X-ray spectroscopy (SEM-EDX) for their morphology. The interactive effect of dosage (43-157 g) and flowrate (2-17 L/hr) was further assessed via a packed-bed column filter. Based on the result, immobilised E.Cottonii sp. showed promising performance for copper removal. The result indicated that the model fits the data with a coefficient of determination (R2 = 0.9844). The optimum conditions for a higher removal of copper using immobilised E.Cottonii sp. were a dosage = 60 g and a flow rate = 5 L/hr for 51.3% removal. In conclusion, the use of E Cottonii sp. as a potential biosorbent for copper removal could pave the way for sustainable environmental technologies.